Dinâmica dos sistemas de produção familiares da Ilha de Marajó: o caso do município de Cachoeira do Arari - BARBOSA, Tienne Milena Farias (2005)
The traditional Amazonian is the Rivers Amazonian. It is a spacial and economic occupation standard very important for regional development. The empirical general space of this research is the Marajó Archipelago, part of the Rivers’ Amazonian. The Amazonian spacial organization has changed in the past years. This change contains a lot of dynamics about the agriculture productive systems and complex economic, social and ambient results. Many realized studies have produced different interpretations about the agriculture activities support in the brazilian and international Amazon. For example, some studies of cattlebreeding to the bovines and buffalo identify that this activity is not been practiced only in the big establishments, like in the past decades. The “pecuarização” process brought it into the little scale creation in familiar economy. This research approaches fundamentally which dynamics have been processed or formed in the municipality of Cachoeira do Arari, situated in Marajó Island-PA, specially from 1994 to 2004. The work was carried with peasant families from six communities (Bacuri, Camará, Caracará, Gurupá, Jabuti and Retiro Grande). The principal objective of this work was to characterize the socioeconomic dynamics occurred in the above period. The results of this study can subsidize future researches and public politics that seek the agriculture production support perspectives. It was used a methodology based in three important aspects: the production system diversity study; the photography through a typology of the production system dynamic study; and the movie through the typology evolution analysis. The identified types as results from the making up data were: subsistence, açaizeiro, abacaxizeiro, pecuaçaí, pecuarista and outrarenda. This study verified a great variation of production systems and identified different dynamics in proprieties, as well as the determining facts of viability of production systems and public policies demands.